Programas de dessecação em coberturas vegetais de inverno e interferência em plantas daninhas e na cultura da soja - Donini, Alberto Luiz Dalcin Alberto Luiz Dalcin (2019)
One of the most important environmental stresses in soybean crop [Glycine max (L.) Merr.] is the competition exerted by weeds. Therefore, the use of herbicides to control them is, still, a priority and it is carried out on a large scale. On the other hand, the use of winter cover crops, in the period prior to soybean cultivation, has several benefits, not only in the management of weeds, and in the development reduction of herbicide resistance. However, the success of cover crops depends on the adoption of an adequate desiccation program to control weeds and, still, allow optimal conditions for the succession sowing crop. Then, the objective of this study was to verify if the desiccation program efficiency on weeds, and on soybean crop, depends on the type of winter cover crop. Therefore, an experiment was carried out to evaluate: (1) if the winter cover crops, from species of different functional groups, grown in pure stands or in mixtures, differ in the accumulation of biomass; (2) if there are simultaneous effects, regarding desiccation program and winter cover crop, on weed infestation and volunteer plants in soybean crop and (3) if there is growth interaction between desiccation program and winter cover crop on growth, yield and yield components of soybean. The experimental design was in a two factorial model (vegetal coverings: fallow, white oat, black oat, radish, small vetch, rye, black oat + radish and black oat + small vetch) x 3 [desiccation programs according to the sum of days before sowing of soybean (DBS): a) sequential application of glyphosate + clethodim at 20 DBS + paraquat at 2 DBS; b) glyphosate + clethodim at 20 DBS and c) glyphosate + clethodim at 10 DBS]. The treatments were arranged in split plot design (plot: winter cover crops; subplot: desiccation program), with four replications. It was observed that the smallest density of weeds (weeds + voluntary plants) was found in rye residues in the three types of desiccation programs. On the other hand, the worst soybean stand occurred in winter covering with radish and radish + black oat. Grain yield presented no significant interaction between the factors tested, only simple effect for both. In the average desiccation program, the lowest soybean yield occurred after radish and black oat + radish cultivation; otherwise, the highest yields were after succession of rye, small vetch, black oat and black oat + small vetch cultivation. The efficiency of desiccation programs depends on the type of cover crops to suppress weed plants in the soybean crop. The rye is versatile in the desiccation program, being effective in controlling weeds on soybean crop under sequential or single application. On the other hand, the control of weeds by radish, black oat and consortia of this grass with small vetch or radish is more effective under sequential desiccation. However, it is necessary to make choices, so that cover crops do not become a drawback for the subsequent crop in the event of natural reseeding.